Peran Mahasiswa KKN UIN SU Kelompok Desa Stabat Lama dalam Mewujudkan Moderasi Beragama, Pencegahan Stunting, dan Pengentasan Kemiskinan Ekstrem di Desa Stabat Lama - Lies Utami Efni Safitri; Habib Munawir Hasibuan; Fatirrohman Alamsyah; Fithri Az-Zahra; Saibarani Nabila (Pusat Riset dan Inovasi Nasional, 2025)
This article examines the role of students of the Real Work Lecture (KKN) of the State Islamic University of North Sumatra in Stabat Lama Village in supporting community development through an integrative approach that covers three main areas, namely religious moderation, stunting prevention, and extreme poverty alleviation. The religious moderation program is carried out through Maghrib Mengaji, Gebyar Islami, and interfaith dialogue, which has been proven to strengthen tolerance and social harmony in the community. The stunting prevention program is realized through the provision of supplemental food (PMT) based on local ingredients, which is able to improve the nutritional status of toddlers while preventing the risk of new stunting. Furthermore, the community economic empowerment program is carried out through ecoprint training with eco pounding techniques that produce works of selling value and open up opportunities for environment-based businesses. The results of the activities show that the three programs complement each other and contribute to improving health, economic independence, and socio-religious harmony. The real impact of the implementation of this program is not only felt in the short term, but also provides the foundation for the development of a more independent and sustainable society. Through the active involvement of students, KKN activities succeeded in connecting academic theory with real practice in the field, so that it was able to provide contextual solutions to village problems. The empowerment carried out also emphasizes inclusive community participation, especially vulnerable groups such as housewives and toddlers, so as to provide more equitable benefits. Thus, KKN in Stabat Lama Village represents a holistic, sustainable, and relevant service model to the achievement of the Sustainable Development Goals (SDGs).